The Shirley estate 1814-1906 : the development and demise of a landed estate in County Monaghan - O'Reilly, Lorraine (Trinity College (Dublin, Ireland). Department of History, 2014)
The following is a study of the semi-absentee Shirley estate situated in south Ulster in the barony of Farney, County Monaghan 'on the edge of a great belt of drumlins that sweep from County Down to North Connaught’. The Shirley family were the largest landowners in Monaghan, possessing 26,386 statute acres in the 1870s and they were closely followed by the neighbouring Bath estate which then comprised of 22,762 acres. It would be easy to assume that both landlords were similar and in some respects they were, especially regarding the management of their estates in Monaghan, but in England, they were very different. The Shirleys for example were never given a peerage, while the Baths held the title of marquis from 1789. In terms of the possession of land, the Baths possessed a much more extensive property portfolio than the Shirleys. In England, they owned large tracts in Wiltshire, Somerset, Hereford, Shropshire and Sussex which, together with the Irish estate, totalled 55,574 acres; by comparison the Shirleys possessed just 1,769 acres in Ettington, Warwickshire, and 665 acres in Worcester. This echoes a point made by L.P. Curtis that the history of individual estates varied as much as the people who lived on them and that it was not unusual to find 'estates in the same barony undergoing different experiences during good times and bad'. This single estate study will not only reflect on Curtis' theory in comparing the two estates at pivotal stages throughout the nineteenth-century but it will demonstrate the value of focussing on a single great estate that was geographically located in the south Monaghan hinterland of Ulster but had characteristics comparable to great landed estates in the west of Ireland.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin